2015
DOI: 10.1016/j.pjnns.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban 10mg/d in severe renal failure does not prevent ischemic events in premorbid neurologic disease

Abstract: In cases of stroke, renal failure and inadequate anticoagulation it is not useful to change from vitamin-K-antagonists to "low dose" DOAC. Diligent investigations for the cause of INR-instability and continuation of vitamin-K-antagonist therapy seem to be more effective and safer since there is the opportunity of monitoring therapy and to avoid under- as well as over-dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition to these subgroup analyses, there is one published case report from Austria of an 82-year-old woman with a history of NVAF treated with rivaroxaban, which appeared to be ineffective 30. The patient was given rivaroxaban therapy at 10 mg daily after hospitalization for ischemic stroke, and it was reported that she was unable to achieve stable INR with warfarin therapy.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these subgroup analyses, there is one published case report from Austria of an 82-year-old woman with a history of NVAF treated with rivaroxaban, which appeared to be ineffective 30. The patient was given rivaroxaban therapy at 10 mg daily after hospitalization for ischemic stroke, and it was reported that she was unable to achieve stable INR with warfarin therapy.…”
Section: Resultsmentioning
confidence: 99%